The meaning of complementary therapy from the perspective of Thai women with breast cancer - Sirisupluxana P. (2014)
A qualitative study based on Heideggerian phenomenology was conducted with 17 Thai women who had survived breast cancer and had utilized at least one type of complementary therapy. The study explored the meaning of such therapy and the data were collected by an in-depth interview, a demographic data-recording form, and a reflective journal. The data were analyzed by using an interpretative process that was described by Cohen, Kahn, and Steeves. Six themes were generated in relation to the meaning of complementary therapy as perceived by the participants: cancer-controlling treatment; mental strengthening; mind and body therapy; self-determination; natural therapy; and conventional therapy integration. The knowledge gained from this study will help health-care providers better understand the role that complementary therapies play in the lives of women whose lives are threatened by cancer. It is important for health-care providers to be more proactive in the culturally sensitive promotion of using complementary therapies based on the women's values and preferences. © 2009 The Authors Journal compilation © 2009 Blackwell Publishing Asia Pty Ltd.